IJCM_163A: A qualitative analysis of awareness regarding type-2 diabetes mellitus among diabetic patients in selected field practice areas of a tertiary care hospital in Mangaluru - Kumar Meera P; Rashmi Anusha; Ummer Farzana (Wolters Kluwer Medknow Publications, 2024)
Background: The prevalence of diabetes is high and growing worldwide, especially in developing countries like India. Over 25 million Indians are prediabetics while an estimated 77 million Indians over the age of 18 have the illness. More than half of the population will have health issues if diabetes is not detected and treated right away. Diabetes awareness, assessment, and practice on an individual basis are essential for early identification and efficient care. Objective: To assess the knowledge regarding diabetes among type 2 Diabetes mellitus patients in the field practice areas of a tertiary care hospital in Mangaluru and to explore their socio-demographic characteristics. Methodology: This is a facility-based, cross-sectional study among a minimum of 40 Type-2 Diabetes mellitus patients from the field practice areas of a tertiary care hospital in Mangaluru. Systematic qualitative method of free listing and pile sorting using interview guide is employed to assess the knowledge while a questionnaire is used to assess socio-demographic profile. Free listing analysis of transcribed data is done using Smith's S or Salience Index while descriptive statistics is used to calculate the mean, standard deviation and the frequencies. Results: In this study, we found out that the majority of participants think the general reasons leading on to diagnosis of Diabetes mellitus are either tiredness/body ache or by blood/ doctor check-up and the reason for being diagnosed were mostly perceived to be unknown or due to tension or consumption of sugar/cool drinks. Significant proportion of participants were observed to show adherence to frequent follow-up of monthly once. Conclusion: In conclusion, though the considerable portion of Type-2 Diabetes mellitus patients adhere to regular follow-up, the knowledge regarding the reasons leading on to the diagnosis or perceived reason for being diagnosed is still lacking. Prompt initiatives are therefore needed to promote awareness towards diabetes among patients.